ANALISIS KEPUASAN KONSUMEN ATAS PELAYANAN HOTEL MEKARSARI INDAH CILEUNGSI - Siagian, Julesron; Panjaitan, Robert P; Hutapea, Ganda T (Universitas Kristen Indonesia, 2016)
The number of visitors has decreased in February to April 2016 and increased again in May 2016. The number of visitors nine in May 2016, in 2895 the number of visitors and the lowest occurred in April 2016, 2647 people. Total visitor Hotel Mekarsari Indah, Cullinan period January - May 2016 was 15 557 people. This study aims to determine the extent of consumer satisfaction level of importance and performance Mekarsari Indah Hotel, Cullinan and to find out what attributes the causes of customer satisfaction Hotel Mekarsari Indah, Cullinan. Source data used are primary data obtained through questionnaires to 100 respondents, ie customers who visited Hotel Mekarsari Indah, Cullinan while secondary data obtained through library research by reading marketing books and other data sources that are still associated with researchKeyword : Performance ,Customer satisfaction